Supply chain strategy during the COVID-19 terms: sentiment analysis and knowledge discovery through text mining - Muhammad Khahfi Zuhanda; Yuan Anisa; Desniarti Desniarti; Muhammad Hafiz; Anil Hakim Syofra; Rezzy Eko Caraka; Maengseok Noh (Institute of Advanced Engineering and Science, 2023)
The coronavirus pandemic has affected not only health but also the economy. The use of big data in finding information can be used to gain profits that logistics companies can utilize to survive during the pandemic. This study conducted text-mining research on service consultant sites in the logistics sector. This study aims to present frequency diagrams, analyze sentiment using the National Research Council (NRC) lexicon, present bigrams, and seek knowledge about strategies to minimize shipping costs and maintain inventories of manufactured goods. The words